Bermain dengan ubin meningkatkan pemahaman koordinat kartesius bagi siswa kelas VI sekolah dasar - Josep Tri Harnanto (Jurnal Pendidikan Dasar, 2022)
Cartesian coordinate material in mathematics is sometimes difficult for students to understand. Teachers also have to be creative in choosing learning models. The author of this article has put into practice a learning model that makes students active, happy, and able to quickly understand the material. Take a look at the learning model in this article.